2019
DOI: 10.26508/lsa.201900328
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-intrinsic response to IFNγ shapes the tumor microenvironment and anti–PD-1 response in NSCLC

Abstract: Targeting PD-1/PD-L1 is only effective in ∼20% of lung cancer patients, but determinants of this response are poorly defined. We previously observed differential responses of two murine K-Ras–mutant lung cancer cell lines to anti–PD-1 therapy: CMT167 tumors were eliminated, whereas Lewis Lung Carcinoma (LLC) tumors were resistant. The goal of this study was to define mechanism(s) mediating this difference. RNA sequencing analysis of cancer cells recovered from lung tumors revealed that CMT167 cells induced an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 39 publications
0
27
1
Order By: Relevance
“…The sensitivity of tumor cells to IFN-γ can play a critical role in the response to PD-1/PD-L1 blockade, which was demonstrated on lung cancer cell lines [48]. However, our data provide evidence that deactivated IFN-γ signaling may not be sufficient for PD-L1 and MHC-I reduction on tumor cells and resistance to PD-L1 blockade.…”
Section: Discussionmentioning
confidence: 57%
“…The sensitivity of tumor cells to IFN-γ can play a critical role in the response to PD-1/PD-L1 blockade, which was demonstrated on lung cancer cell lines [48]. However, our data provide evidence that deactivated IFN-γ signaling may not be sufficient for PD-L1 and MHC-I reduction on tumor cells and resistance to PD-L1 blockade.…”
Section: Discussionmentioning
confidence: 57%
“…We previously reported that the CMT167 and LLC mouse models of NSCLC differ in their response to PD-1-targeted immunotherapy, with divergent IFNγ signatures in vivo. 31 To further examine this, we assessed the ability of these cells to respond to in vitro IFNγ stimulation, measuring protein expression at the single-cell level. CMT167 and LLC cells were cultured under either basal or IFNγ stimulated conditions and subjected to mass cytometry, with cellular phenotypes characterized using the PhenoGraph clustering algorithm, visualized using the tSNE dimensionality reduction approach.…”
Section: Resultsmentioning
confidence: 99%
“…The relative message levels of each target gene were normalized to GAPDH. 31 20 All statistical analyzes were done using GraphPad Prism software. Specific statistical tests performed are described in figure legends, with statistical significance defined if p<0.05.…”
Section: Quantitative Real-time-pcrmentioning
confidence: 99%
“…Ayers et al have developed a gene signature involving responsiveness to interferon gamma (IFNγ) associate with response (Ayers et al, 2017). Our lab has demonstrated that at least in mouse models of lung cancer responsiveness to IFNγ is a determinant of response to anti-PD-1 therapy (Bullock et al, 2019).…”
Section: Regulators Of Tumor Immunitymentioning
confidence: 99%